Beyond the box : B.F. Skinner's technology of behavior from laboratory to life, 1950s-1970s - Rutherford, Alexandra, 1971- (University of Toronto Press, 2009)
Beyond the Box is the first full-length study of the ways in which Skinner's ideas left the laboratory to become part of the post-war public's everyday lives, and chronicles both the enthusiasm and caution with which this process was received.
Keywords: Skinner, B. F. -- (Burrhus Frederic), -- 1904-1990.; Skinner, B. F -- (Burrhus Frederic), -- 1904-1990.; Skinner, B. F. -- (Burrhus Frederic), -- 1904-1990; Behaviorism (Psychology); Behaviorism -- history; History, 20th Century; Behaviorism; Béhaviorisme (Psychologie); Médecine -- Histoire -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; PSYCHOLOGY -- Movements -- Behaviorism.; MEDICAL -- History.